Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the equation [tex]\(-3 \tan^2(x) + 1 = 0\)[/tex], let’s go through the process step by step.
1. Isolate [tex]\(\tan^2(x)\)[/tex]:
[tex]\[ -3 \tan^2(x) + 1 = 0 \][/tex]
[tex]\[ -3 \tan^2(x) = -1 \][/tex]
[tex]\[ \tan^2(x) = \frac{1}{3} \][/tex]
2. Take the square root on both sides:
[tex]\[ \tan(x) = \pm \sqrt{\frac{1}{3}} \][/tex]
[tex]\[ \tan(x) = \pm \frac{1}{\sqrt{3}} \][/tex]
Simplifying, we get:
[tex]\[ \tan(x) = \pm \frac{\sqrt{3}}{3} \][/tex]
3. Identify the angles whose tangent values are [tex]\(\frac{\sqrt{3}}{3}\)[/tex] and [tex]\(-\frac{\sqrt{3}}{3}\)[/tex]:
[tex]\(\tan(x) = \frac{\sqrt{3}}{3}\)[/tex] occurs at [tex]\(x = \frac{\pi}{6} + k\pi\)[/tex], where [tex]\(k\)[/tex] is any integer.
[tex]\(\tan(x) = -\frac{\sqrt{3}}{3}\)[/tex] occurs at [tex]\(x = \frac{5\pi}{6} + k\pi\)[/tex], where [tex]\(k\)[/tex] is any integer.
4. Combine the two sets of solutions:
Therefore, the complete set of solutions to the equation [tex]\(-3 \tan^2(x) + 1 = 0\)[/tex] in radians is:
[tex]\[ x = \frac{\pi}{6} + k\pi \quad \text{and} \quad x = \frac{5\pi}{6} + k\pi \quad \text{for integer } k \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\frac{\pi}{6} + k\pi \quad \text{and} \quad \frac{5\pi}{6} + k\pi} \][/tex]
1. Isolate [tex]\(\tan^2(x)\)[/tex]:
[tex]\[ -3 \tan^2(x) + 1 = 0 \][/tex]
[tex]\[ -3 \tan^2(x) = -1 \][/tex]
[tex]\[ \tan^2(x) = \frac{1}{3} \][/tex]
2. Take the square root on both sides:
[tex]\[ \tan(x) = \pm \sqrt{\frac{1}{3}} \][/tex]
[tex]\[ \tan(x) = \pm \frac{1}{\sqrt{3}} \][/tex]
Simplifying, we get:
[tex]\[ \tan(x) = \pm \frac{\sqrt{3}}{3} \][/tex]
3. Identify the angles whose tangent values are [tex]\(\frac{\sqrt{3}}{3}\)[/tex] and [tex]\(-\frac{\sqrt{3}}{3}\)[/tex]:
[tex]\(\tan(x) = \frac{\sqrt{3}}{3}\)[/tex] occurs at [tex]\(x = \frac{\pi}{6} + k\pi\)[/tex], where [tex]\(k\)[/tex] is any integer.
[tex]\(\tan(x) = -\frac{\sqrt{3}}{3}\)[/tex] occurs at [tex]\(x = \frac{5\pi}{6} + k\pi\)[/tex], where [tex]\(k\)[/tex] is any integer.
4. Combine the two sets of solutions:
Therefore, the complete set of solutions to the equation [tex]\(-3 \tan^2(x) + 1 = 0\)[/tex] in radians is:
[tex]\[ x = \frac{\pi}{6} + k\pi \quad \text{and} \quad x = \frac{5\pi}{6} + k\pi \quad \text{for integer } k \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{\frac{\pi}{6} + k\pi \quad \text{and} \quad \frac{5\pi}{6} + k\pi} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.